ASSESSMENT OF GENETIC PARAMETERS IN MAIZE (Zea mays L.) FOR YIELD AND ASSOCIATED TRAITS: ASSESSMENT OF GENETIC PARAMETERS IN MAIZE (Zea mays L.) FOR YIELD AND ASSOCIATED TRAITS - N. SAI UDAY YOGITHA; Y. SATISH; Y. PUSHPA RENI; G. VIJAYA KUMAR (The Journal of Research ANGRAU, 2026)
The present study was undertaken during the rabi season of 2024–25 at the Regional Agricultural Research Station (RARS), Lam, Guntur, Andhra Pradesh, to evaluate the extent of genetic variability, heritability and genetic advance in maize (Zea mays L.) inbred lines. A total of 50 inbred lines comprising 48 test entries along with two standard checks (LM 13 and LM 14) are assessed using alpha lattice design with two replications. Data was recorded on thirteen quantitative traits encompassing phenological, morphological and yield-related parameters. Analysis of variance revealed highly significant differences among the genotypes for all the traits studied indicating the presence of considerable genetic variability. The phenotypic coefficient of variation (PCV) exceeded the genotypic coefficient of variation (GCV) for all traits, reflecting the influence of environmental factors on trait expression. High estimates of GCV and PCV were observed for ear height, 100-kernel weight and grain yield per plant suggesting the existence of substantial variability within the genetic material. Moderate variability was recorded for plant height, ear length and SPAD chlorophyll meter reading, whereas relatively low variability was observed for days to 50% anthesis, days to 50% silking and days to maturity. High heritability coupled with high genetic advance as per cent of mean was recorded for plant height, ear height, number of kernels per row, 100-kernel weight and grain yield per plant indicating the predominance of additive gene effects and the potential effectiveness of direct selection for these traits. Moderate heritability with moderate genetic advance was observed for ear length, ear girth, number of kernel rows per ear and SPAD chlorophyll meter reading, suggesting the involvement of both additive and nonadditive gene actions.